ANALISIS PROFITABILITAS USAHATANI CABAI MERAH (Capsicum annuum) DI DESA GOMBONG KECAMATAN BELIK KABUPATEN PEMALANG - Wiit Rismawanto; Sulistyani Budiningsih; Watemin Watemin (Universitas Muhammadiyah Purwokerto, 2016)
The study aimed to determine the profitability of red chili farming (Capsicum annuum) in Gombong village, Belik District, Pemalang. The study applied purposive sampling method on 60 samples of red chili farmers. The results showed that the cost of farm production of red chili in Gombong village, Belik District, Pemalang regency was divided into two: the fixed costs and variable costs. The average of fixed cost in farming red chili was Rp.2.546.049,325/Ut/Mt, while the average variable cost was Rp.23.916.678/Ut/Mt. Thus, the average total cost of production in the farming red chili was Rp.26.462.727,325/Ut/Mt, then the production costs per kg spent by the farmer in the village of red chili farming Gombong, Belik District, Pemalang regency was Rp.11.132,825/kg. Profitability is the ability of a company to generate (profit) on thelevel of sales, assets, and a specific share capital. In the study, red chili farming in Gombong village, Belik District, Pemalang obtained 14,547 % profits.